(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Many companies today, especially Iraqi companies, have a functionally fragmented supply chain. Costs are disclosed only at each stage of the individual supply chain, leading to a product at a higher cost and a longer delivery time, and is not compatible with the change and diversity of customers’ needs and desires. , So there is an increasing need for performance management along the total supply chain. This has led to the emergence of TD-ABC technology, which plays a major role in cost-effectively managing the product through its supply chain in an integrated and continuous manner, providing the lowest cost, And Get a competitive advantage